Persepsi Guru terhadap Jogja Madrasah Digital - Finan Ahsani Taqwim; Umi Habibah; Faishal Ackmal Survanta; Zainal Arifin Ahmad (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to analyze the implementation of education digitalization policy through the Jogja Madrasah Digital (JMD) program initiated by the Regional Office of the Ministry of Religious Affairs of the Special Region of Yogyakarta. Using a quantitative dan qualitative approach, the research involved 84 teachers from eight madrasahs as respondents. Correlation and reliability analyses using SPSS revealed that all variables were positively and significantly correlated (p < 0.01), with a Cronbach’s Alpha value of 0.967 indicating very high instrument reliability. The findings show that most teachers have positive perceptions of the usefulness, ease of use, and attitude toward JMD and intend to continue using it. Despite technical issues such as server stability and infrastructure limitations, JMD has proven to enhance efficiency, transparency, and learning quality. The study recommends strengthening server capacity, improving system security, adding collaborative features among madrasahs, providing an offline mode, and ensuring accessibility for visually impaired students to support sustainable digital education transformation.